The crystal structure of (1E,2E)-1,2-bis(quinolin-2-ylmethylene)hydrazine, C20H14N4 - Liao Fuguang; Yuan Shuhao; Nie Weifeng; Yi Zirong; Zhang Qian; Yan Shiyu; Cui Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C20H14N4, monoclinic, P21/c (no. 14), a = 13.4569(16) Å, b = 4.7592(5) Å, c = 11.9902(13) Å, β = 94.914(2)°, V = 765.08(15) Å3, Z = 2, R gt(F) = 0.0333, wR ref(F 2) = 0.0935, T = 296(2) K.